Parathyroid disorder and concomitant thyroid cancer in patients with multiple endocrine neoplasia type 1: A retrospective cohort study. Issue 36 (10th September 2021) - Wang, Ying; Cai, Sheng; Liu, He; Zhao, Rui-Na; Lai, Xing-Jian; Lv, Ke; Jiang, Yu-Xin; Li, Jian-Chu
Abstract : Abstract: This study aimed to determine the rates and characteristics of parathyroid disorder and thyroid cancer in patients with multiple endocrine neoplasia type 1 vs sporadic primary hyperparathyroidism (SPHP) undergoing parathyroidectomy. Patients with multiple endocrine neoplasia type 1-associated primary hyperparathyroidism (MPHP) or SPHP who underwent initial or reoperative parathyroid exploration from 1999 to 2019 were identified via a clinical database. The data for MPHP patients (n = 15) were compared to those of a selected 2:1 age- and sex-matched SPHP cohort (n = 30) who all underwent thyroidectomy for concurrent thyroid nodules. Compared with that of the SPHP group, the parathyroid hormone level of the MPHP group was much higher (470.67 ± 490.74 pg/mL vs 217.77 ± 165.60 pg/mL, P  = .001). Multiglandular parathyroid disease (6/15 [40%] vs 3/30 [10%], P  = .026) and more hyperplasia (7/15 [46.7%] vs 5/30 [16.7%], P  = .039) were found in the MPHP group, and more parathyroid lesions presented as a round shape (long/short meridian < 2) by ultrasound (16/20 [80%] vs 8/31 [25.8%], P  < .001). Regarding thyroid nodules, there was no difference in the rate of histologic thyroid cancer, but more thyroid cancer was found in the last 5 years among the MPHP cases (5/9 [55.6%] vs 3/18 [16.7%], P  = .052). Multiglandular parathyroid disease and hyperplasia were more frequent in the MPHP cohort than in the SPHP cohort, and the parathyroid lesions usually presented with a round shape on ultrasonography. More concurrent thyroid cancer was found in MPHP than SPHP patients over the previous 5 years.